Pengaruh Pendekatan Tarl Terhadap Hasil Belajar Pada Mata Pelajaran IPAS Kelas IV SDN Sawah Besar 01 Semarang - Anggraini, Erika Yusi Novita; Subekti , Ervina Eka; Lestari , Alberta Budi (LPPM Universitas PGRI Argopuro Jember, 2024)
The aim of this research is to determine whether or not there is an influence of the Tarl approach on learning outcomes in science and science subjects for class IV students at SDN Sawah Besar 01 Semarang. This type of research is experimental. The research design used was Pre-Experimental Design with a One-Group Pretest-Posttest Design model. The subjects of this research were class IV students with a total of 29 students. The data collection methods used were tests, interviews and observations. The results of this research show the influence of the Tarl approach on learning outcomes in class IV science subjects at SDN Sawah Besar 01 Semarang. This is based on the results of the t-test carried out, that the probability or significance level (2-tailed) of class IV student learning outcomes at SDN Sawah Besar 01 is 0.000 < 0.05. So, Ha accepted. This means that there is an influence of implementing the approach on the mathematics learning outcomes of grade IV students at SDN Sawah Besar 01.